Un Sdgs And The Modern Consumer: A Study On Sustainable Decision-Making (International Journal of Environmental Sciences, 2025)
The United Nations (UN), established to uphold international peace, security, and global cooperation, introduced the sustainable development goals (SDGs) in 2015 as part of the 2030 Agenda for sustainable Development. These 17 global objectives aim to promote environmental preservation, ethical development, and technological advancement in a balanced and sustainable manner. As environmental degradation intensifies due to rapid technological progress and lifestyle shifts, there is a growing emphasis on sustainable consumption. Consumers are increasingly leaning toward environmentally responsible choices, influenced by heightened awareness of sustainability and the global green movement. The study examines the influence of the UN SDGs on consumer decision making by particularly focusing on how awareness and corporate integration of these goals affect consumer preference in Indian market. It explores the role of SDG aligned practices by businesses in shaping consumer behavior, while also identifying the barriers that prevent widespread adoption of sustainable choices. The study has been conducted by considering both primary and secondary data whereas primary data collected among 129 consumers by involving both aware and unaware consumers of SDGs and the collected data has been analyzed using SPSS. The findings provide insights into the extent to which sustainability awareness impacts the purchasing decisions and the challenges which remain in embedding SDG oriented thinking in consumer behavior.